Effect of a Discrete PIN Diode on Defected Ground Structure - Abdul Hadi, M. H.; Ahmad, B. H.; Shairi, N. A.; Wong , Peng Wen (2013)
Abstract—This paper investigates the effect of a discrete PIN diode on Defected Ground Structure (DGS) where the different resonant frequency between ON and OFF state of the PIN diode is observed. Analytical modeling is determined and analyzed based on equivalent circuit of PIN diode and DGS. Then, a circuit simulation is performed using simulation software with different value of inductance and capacitance of DGS during ON and OFF state of the PIN diode. As a result, the resonant frequency of the PIN diode on the DGS shifted to higher frequency during ON state and shifted to lower frequency during OFF state. Besides, a larger value of inductance with a smaller value of capacitance of DGS will produce a larger range of resonant frequency between ON and OFF state and vice versa.